ANTIOXIDANT ACTIVITY TEST OF ETHANOL EXTRACT (Polycarpa aurata) OBTAINED FROM THE WATERS OF POOPOH VILLAGE, MINAHASA REGENCY - Ghanny, Ath Thariq Fadhli Adhimul Ghanny; Yudistira, Adhitya; Lebang, Julianri Sari (UNIVERSITAS SAM RATULANGI, 2024)
One of the potential marine ingredients that are needed in the fields of food, cosmetics and health is as a source of antioxidants. Antioxidants inhibit the decay of certain substances, reduce oxidative stress, inhibit cell aging, and ward off free radicals. One marine organism that has potential as a natural antioxidant is Tunikata Polycarpa aurata. This study aims to test the antioxidant activity of Polycarpa aurata ethanol extract obtained from the coast of Poopoh Village, Minahasa Regency. The test uses the DPPH method with concentrations of 25 ppm, 50 ppm, 75 ppm, and 100 ppm to analyze antioxidant activity using a spectrophotometer. The results obtained the greatest antioxidant activity in Polycarpa aurata with a concentration of 100 ppm with an average percent inhibition of 80.744%. The results of this study showed the antioxidant activity of Polycarpa aurata from the waters of Poopoh Village, Minahasa Regency has good antioxidant activity. Keywords: Polycarpa aurata, Antioxidant, DPPH, Poopoh Village, Minahasa Regency.